Taxation and Market Power - Florian Morath; Kai A. Konrad; Wieland Müller (Verein für Socialpolitik, 2010)
We analyze the incidence and welfare effects of unit sales taxes in experimental monopoly and Bertrand markets. We find, in line with economic theory, that firms with no market power are able to shift a high share of a tax burden on to consumers, independent of whether buyers are automated or human players. In monopoly markets, a monopolist bears a large share of the burden of a tax increase. With human buyers, however, this share is smaller than with automated buyers as the presence of human buyers constrains the pricing behavior of a monopolist.
Keywords: H22; L12; L13; 330; tax incidence; monopoly; Bertrand competition; experiment